Shared Decision-Making : Can Improved Counseling Increase Willingness to Pay for Modern Contraceptives? - Athey, Susan (World Bank, Washington, DC, 2021)
Long-acting reversible contraceptives are highly effective in preventing unintended pregnancies, but take-up remains low. This paper analyzes a randomized controlled trial of interventions addressing two barriers to long-acting reversible contraceptive adoption, credit, and informational constraints. The study offered discounts to the clients of a women’s hospital in Yaoundé, Cameroon, and cross-randomized a counseling strategy that encourages shared decision-making using a tablet-based app that ranks modern methods. Discounts increased uptake by 50 percent, with larger effects for adolescents. Shared decision-making tripled the share of clients adopting a long-acting reversible contraceptive at full price, from 11 to 35 percent, and discounts had no incremental impact in this group.